Genome Context Influences Evolutionary Flexibility of Nearly Identical Type III Effectors in Two Phytopathogenic Pseudomonads - Baltrus, David A.; Feng, Qian; Kvitko, Brian H. (Frontiers in Microbiology, 2022)
Integrative Conjugative Elements (ICEs) are replicons that can insert and excise from chromosomal locations in a site specific manner, can conjugate across strains, and which often carry a variety of genes useful for bacterial growth and survival under specific conditions. Although ICEs have been identified and vetted within certain clades of the agricultural pathogen Pseudomonas syringae, the impact of ICE carriage and transfer across the entire P. syringae species complex remains underexplored. Here we identify and vet an ICE (PmaICE-DQ) from P. syringae pv. maculicola ES4326, a strain commonly used for laboratory virulence experiments, demonstrate that this element can excise and conjugate across strains, and contains loci encoding multiple type III effector proteins. Moreover, genome context suggests that another ICE (PmaICE-AOAB) is highly similar in comparison with and found immediately adjacent to PmaICE-DQ within the chromosome of strain ES4326, and also contains multiple type III effectors. Lastly, we present passage data from in planta experiments that suggests that genomic plasticity associated with ICEs may enable strains to more rapidly lose type III effectors that trigger R-gene mediated resistance in comparison to strains where nearly isogenic effectors are not present in ICEs. Taken together, our study sheds light on a set of ICE elements from P. syringae pv. maculicola ES4326 and highlights how genomic context may lead to different evolutionary dynamics for shared virulence genes between strains.